Physical Activity Levels, Exercise Attitudes, Self-Perceptions, Nutritional Behaviors and BMI Type of 12-Years Children - Digelidis, Νικόλαος; Kamtsios, Σπυρίδων; Theodorakis, Ιωάννης (Inquiries in Physical Education and Sport, 2007)
The purpose of this study was to examine the differences among pupils of the elementary school, with different body mass index (BMI) as to: a) the attitudes towards exercise, b) self-perceptions, c) lesson satisfaction in physical education, d) nutritional behaviours and e) their participation in physical activity. In this study 775 pupils participated (362 boys and 413 girls), aged 11-12 years. The study was held through questionnaires and all scales had acceptable levels of internal consistency (α>.67). Students were divided according to their BMI, to those with: a) normal BMI, b) overweight children and c) obese children. The 23,6% and 3,6% of those pupils were categorized as overweight and obese accordingly. Two-way anova was used,with gender and BMI type as independent variables in order to examine differences. The results revealed that the obese and overweight pupils, when compared with students with normal BMI, had lower scores in lesson satisfaction, they have negative view for their body and reduced level on their participation of physical activity. Also, the results showed that they adopt more sedentary daily habits such as: many hours of TV watching and PC usage.